(3TQM CdajI GHf eGdcs - (3CHhYHO Gddg TeS GdOjf eMeO Hf CMeO Hf LGHQ GdghGQj GdCfOdSj GdeGdcj GdVQjQ GdfMhjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf Yde GdYQHjI ef GdcdGe HefRdI GdedM ef GdWYGe, LYdgG Gddg CTQa GdCdSf GdeJcde HgG aj GdCjGe s
(3BNQgG (B:s
(3hGYde Cf gPg GdCSeGA CjVkG jLhR EVGaJgG Edi GdXGgQ bhdg HGdCda CQaY GdeKfi hcdG EPG HeVQ eVGakG hUdG s
(3ajg VHW bdjds
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdfMhs